Comparative efficacy of non-steroidal anti-inflammatory drugs in preventing postoperative macular edema following cataract surgery: a systematic review and Network Meta-analysis - Min Lang; Jie Xuan; Xue Li; Ming-Ming Liu; Jie Xu; Ting Liu (International Journal of Ophthalmology)
AIM: To assess and rank the efficacy of various non-steroidal anti-inflammatory drugs (NSAIDs) in preventing postoperative macular edema (PME) after cataract surgery. METHODS: A comprehensive search was conducted across PubMed, Embase, Cochrane Library, and Web of Science databases. Randomized controlled trials (RCTs) comparing different NSAIDs and control treatments for the prevention of PME were included. Data from the studies were synthesized using the “gemtc” package in R. Risk of bias was assessed with the Cochrane RoB 2 tool, and heterogeneity was evaluated using the global I2 statistic. Surface under the cumulative ranking curve (SUCRA) values were calculated for each treatment. RESULTS: Of 132 identified records, 9 RCTs met the inclusion criteria. The Network Meta-analysis indicated that nepafenac had the highest efficacy in preventing PME, followed by artificial tear substitute, ketorolac, diclofenac, and bromfenac. The league table comparisons and rankograms corroborated these findings, with nepafenac consistently ranking highest. Heterogeneity analysis yielded high I2 values, indicating substantial variability across studies. CONCLUSION: This Network Meta-analysis suggests that nepafenac is the most effective NSAID for preventing PME following cataract surgery. Given the substantial heterogeneity observed, further high-quality RCTs are required to confirm these findings and explore the sources of variability. Clinicians should consider these results when selecting NSAIDs for PME prophylaxis in cataract surgery patients.